Performance factors related to the health status of PLWHA with HAAR - Rios-Cordova, Sonia (2019)
Determine the relationship between the performance factors and the health status of people living with HIV/AIDS who received HAART, the Regional Hospital in Pucallpa, 2012. Material and methods. The information analyzed part of the list of matching applied to personnel of health that provides HAART, as well as the questionnaire and Likert lifted information on the state of physical and mental health of 41 PLWHA. We found that the 95.1% received information, guidance and appropriate treatment. The 90.2% presented a state of physical and mental health satisfactory. Therefore the performance factors are directly related to the mental and physical state of health of the PLWHA. Conclusions. The results suggest that the PWA should assume responsibility the indications and directions provided by the health staff to maintain a good state of physical and mental health, prevent opportunistic illnesses, improve their occupational activities, sports, recreation, food, rest and sleep; and integration into society.